2018
DOI: 10.4103/eus.eus_7_17
|View full text |Cite
|
Sign up to set email alerts
|

Assessing tumor angiogenesis in colorectal cancer by quantitative contrast-enhanced endoscopic ultrasound and molecular and immunohistochemical analysis

Abstract: Background and Objectives:Data on contrast-enhanced endoscopic ultrasound (CE-EUS) for colorectal cancer (CRC) evaluation are scarce. Therefore, we aimed to assess the vascular perfusion pattern in CRC by quantitative CE-EUS and compare it to immunohistochemical and genetic markers of angiogenesis.Patients and Methods:We performed a retrospective analysis of CE-EUS examinations of 42 CRC patients, before any therapy. CE-EUS movies were processed using a dedicated software. Ten parameters were automatically gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…Finally, the visualization of the anorectosigmoid region during endoscopy of the patient prior to treatment, identifies other colorectal diseases that may be contributing to the symptoms such as bleeding, especially colorectal neoplasia. [ 63 , 64 , 65 ] In the United States, a cohort study based on blood in the stool reported that the incidence of diverticulosis, polyps or multiple polyps, mucosal abnormalities/colitis, tumors, and solitary ulcers were significantly increased in the patients undergoing endoscopy. [ 66 ] In addition, anorectal diseases such as hemorrhoids are very common in patients with intestinal diseases.…”
Section: Advantages Of Endoscopic Hemorrhoid Treatmentmentioning
confidence: 99%
“…Finally, the visualization of the anorectosigmoid region during endoscopy of the patient prior to treatment, identifies other colorectal diseases that may be contributing to the symptoms such as bleeding, especially colorectal neoplasia. [ 63 , 64 , 65 ] In the United States, a cohort study based on blood in the stool reported that the incidence of diverticulosis, polyps or multiple polyps, mucosal abnormalities/colitis, tumors, and solitary ulcers were significantly increased in the patients undergoing endoscopy. [ 66 ] In addition, anorectal diseases such as hemorrhoids are very common in patients with intestinal diseases.…”
Section: Advantages Of Endoscopic Hemorrhoid Treatmentmentioning
confidence: 99%
“…The median score for Ki67 staining was 4 (min–max 3–5) in the high-grade (HG) and 2 (min–max 1–4) in the low-grade (LG) group; for Hif1α, the median score was 2.5 (min–max 1–4) for HG and 2 (min–max 1–5) for LG ( Table 1 and Figure 1 ). The measurement of microvessel density (MVD) is a widely accepted method for assessing angiogenic activity through counting positive staining by anti-CD31 and anti-CD105 [ 10 ]. The median MVD assessed by quantifying presence of CD31 staining was 15.5 (min–max 9–28) in the HG and 19.5 (min–max 6–27) in the LG group.…”
Section: Resultsmentioning
confidence: 99%
“…Under normal conditions, the evaluation of blood supply in the distal rectum and mesorectum shows a predominance of blood vessels within the rectal wall[ 8 ]. In rectal cancer patients contrast-enhanced endoscopic ultrasound imaging usually reveals well vascularized masses with inhomogeneous enhancement of the contrast resulting from necrotic areas[ 9 ]. In the reported case, although atypical, a hypervascularized mass, with a predominance of blood vessels in the mesorectum was observed, as demonstrated by imaging exams.…”
Section: Discussionmentioning
confidence: 99%